The Epistle to the Hebrews - Cockerill, Gareth Lee (The New international commentary on the New Testament, 2012)
"This commentary by Gareth Lee Cockerill offers insight into the Epistle to the Hebrews, a well-constructed sermon that encourages its hearers to persevere despite persecution and hardships in light of Christ's unique sufficiency as Savior. Cockerill analyzes the book's rhetorical, chiastic shape and interprets each passage in light of this overarching structure. He also offers a new analysis of the epistle's use of the Old Testament--continuity and fulfillment rather than continuity and discontinuity--and shows how this consistent usage is relevant for contemporary biblical interpretation"--Publisher description